50 Jahre Universitätspartnerschaft Hamburg - Bordeaux. Präsentation des Jubliäumsbandes und Verleihung der Ehrendoktorwürde an Prof. Dr. Jean Mondot am 30. Oktober 2007 im Warburg-Haus, Hamburg - Stiehl, H. Siegfried; Deininger, Jürgen (Hamburger Universitätsreden Neue Folge, 2008)
The partnership between the Universities of Hamburg and Bordeaux, which has existed for half a century, has been put into practice in many forms. There were two main reasons for the fact that this is the first time in the long history of partnership that an anniversary has been celebrated.One of these was the publication of an extensive anniversary volume, which was produced in close cooperation with the Hamburg-Bordelais historians. The other occasion was the conferral of an honorary doctorate from the University of Hamburg by the Department of Language, Literature and Media (SLM) II to the Bordelaiser German scholar Jean Mondot for his research on European Enlightenment, which set new standards, particularly in Germany.